Synthesis, Characterization and Anti-Inflammatory and Antipyretic evaluation of Novel Indole Derivatives (Journal of Basic and Applied Research in Biomedicine, 2022)
Indole, the bicyclic ring system consists of pyrrole ring fused with benzene ring. Although indole moiety is very small but is fascinated by scientists because of the diverse biological activities by not only indole but its various substituted derivatives as well. In the present study some novel indole derivatives like 6-Chloro-3-[(N,N-diethylamino)(oxo)acetyl]-1-benzyl-N-aryl-1H-indole-5-carboxamide derivatives (IC-1 to IC-10) were synthesized according to the scheme. The synthesized novel indole derivatives have been characterized by using elemental analysis, FT-IR, 1HNMR, 13C NMR spectroscopy and further supported by Mass spectroscopy. Purity of all the compounds has been checked on thin layer chromatographic plate and HPLC technique. All the synthesized compounds were evaluated for anti-inflammatory and antipyreticactivities. All the compounds exhibited moderate to significant anti-inflammatory and antipyreticactivities.